Growth, Poverty and Development Assistance: When Does Foreign Aid Work?. Issue 3 (21st August 2015) - Sumner, Andy; Glennie, Jonathan
Abstract This is a survey paper on aid effectiveness in terms of the contribution of development assistance to economic growth and poverty reduction. The article focuses primarily on the most recent generation of cross‐country studies. It concludes that there is a set of broad areas where the evidence reviewed shows signs of convergence that have direct relevance for policy decisions on aid and for aid‐effectiveness discussions. These areas are: aid levels (meaning if the level of aid is too low or too high); domestic political institutions (including political stability and the extent of decentralisation); the composition of aid (including sectors, modalities, objectives and time horizons); and the volatility and fragmentation of aid. We also identify two areas where there is little sign of convergence in the evidence: the importance or otherwise of 'good', meaning orthodox macroeconomic policies and whether grants are more effective than loans.